Integrating Digital Learning Tools into the Arabic Language Curriculum: Solutions and Success - Faiza Amaliyah; Hasan, Laili Mas Ulliyah (Global Action and Education for Society, 2025)
This article examines the application of digital learning tools in Arabic language curricula and evaluates their effectiveness in improving student skills. With rapid technological advances, the integration of digital tools such as language learning applications, e-learning platforms, and interactive media have become important aspects of modernising Arabic language education. The study explores the range of digital solutions that have been implemented in several educational institutions, as well as evaluating the success of their implementation through a case study approach. The research methodology includes analysis of the use of digital tools, collection of data from surveys, interviews, and evaluation of students' learning outcomes before and after the application of tools. The findings of this study show that digital tools not only enhance student engagement by making the learning process more interesting and interactive, but also significantly improve their learning results. The application of digital tools has proven to provide innovative solutions to the challenges of teaching Arabic, enriching learning experiences, and delivering better results in mastering Arabic language materials.